Learning Emergent Strategies Through Design Thinking. (March 2014) - Fixson, Sebastian K.; Rao, Jay
<x xml:space="preserve">Abstract</x> Analyzing a new business opportunity with traditional business tools, which are based on the logic of predictability, can handicap a new project before it even begins. That's why Babson educators teach emergent strategy, and they do it using design thinking. When the variables are unknown, predicting outcomes a priori with traditional business analytics is often a losing proposition. At Babson College, educators teach emergent strategy, which uses ideation, prototyping, and iteration—tools more familiar to entrepreneurs and design thinkers.